The Role of Mobile Apps in Language Development: Mobile Learning Solutions for Accessible and Flexible Language Education - Rizky Wardhani; Rendy Aditya; Icha Fais Nurul Karimah; Hasan Hasan; Meera Gupta (International Journal of Language and Ubiquitous Learning, 2026)
Background. Mobile technology has rapidly transformed the way language education is delivered, providing learners with flexible, accessible, and personalized learning experiences. Mobile applications (mobile apps) have become essential tools in language development, enabling learners to engage with language content anytime and anywhere. Despite their growing popularity, there is limited research that comprehensively examines the specific role of mobile apps in language development, particularly in terms of accessibility, effectiveness, and learner engagement. Purpose. This study aims to explore the role of mobile apps in enhancing language development by investigating their effectiveness as mobile learning solutions. The research focuses on how mobile apps contribute to language learning accessibility, engagement, and proficiency, and examines their potential for providing flexible, learner-centered educational experiences. Method. The study adopts a mixed-methods approach, combining both quantitative and qualitative data. Surveys and interviews were conducted with language learners who regularly used mobile apps for language development. Language proficiency tests were administered before and after the intervention to measure the impact of mobile apps on language acquisition. The findings indicate that learners who used mobile apps demonstrated significant improvements in language proficiency, particularly in vocabulary acquisition and speaking skills. Results. The results also show increased learner engagement and motivation, with participants reporting that mobile apps made language learning more accessible and enjoyable. Conclusion. Mobile apps play a critical role in language development by offering flexible, accessible, and personalized learning experiences. These apps provide an effective alternative to traditional language learning methods, fostering higher engagement and improved language proficiency.